2015
DOI: 10.1186/0717-6287-48-3
|View full text |Cite
|
Sign up to set email alerts
|

A low-protein diet during pregnancy prevents modifications in intercellular communication proteins in rat islets

Abstract: BackgroundGap junctions between β-cells participate in the precise regulation of insulin secretion. Adherens junctions and their associated proteins are required for the formation, function and structural maintenance of gap junctions. Increases in the number of the gap junctions between β-cells and enhanced glucose-stimulated insulin secretion are observed during pregnancy. In contrast, protein restriction produces structural and functional alterations that result in poor insulin secretion in response to gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…It is also interesting to note that the reductions in GSIS that are induced by treatment with the anti-depressant drug fluoxetine (Prozac) [ 61 ] are also associated with decreases in E-cadherin levels in β-cells [ 62 ]. It has also been observed that mice on a low protein diet have reductions in GSIS that correlate with reductions in β-catenin levels in islets [ 63 ]. We see rapid changes in β-catenin levels in β-cell models in response to acute changes in glucose levels [ 41 ], which could provide a mechanism that would allow glucose levels to regulate the maximum levels of GSIS over the time frame of minutes and hours.…”
Section: Physiological Implications Of Adherens Junction Mediated Regmentioning
confidence: 99%
“…It is also interesting to note that the reductions in GSIS that are induced by treatment with the anti-depressant drug fluoxetine (Prozac) [ 61 ] are also associated with decreases in E-cadherin levels in β-cells [ 62 ]. It has also been observed that mice on a low protein diet have reductions in GSIS that correlate with reductions in β-catenin levels in islets [ 63 ]. We see rapid changes in β-catenin levels in β-cell models in response to acute changes in glucose levels [ 41 ], which could provide a mechanism that would allow glucose levels to regulate the maximum levels of GSIS over the time frame of minutes and hours.…”
Section: Physiological Implications Of Adherens Junction Mediated Regmentioning
confidence: 99%
“…2005; Marçal‐Pessoa et al . 2015). The same diet during pregnancy also reduced maternal islet area in association with reduced PI3K signalling, but no change in insulin content was observed (Salvatierra et al .…”
Section: Introductionmentioning
confidence: 99%